Germplasm resources, genetic diversity, functional genes, genetic breeding, and prospects of Pinellia ternata (Thunb.) Breit: a review - Jingyi Zhang; Ming Luo; Yuhuan Miao; Rong Xu; Mingxing Wang; Jiawei Xu; Dahui Liu (Medicinal Plant Biology, 2023)
Pinellia ternata (Thunb.) Breit. is a traditional Chinese medicinal plant that has been widely used in China, Japan and Korea to relieve cough, vomiting, and inflammation. This review summarizes the recent research focus on germplasm resources, genetic diversity, functional genes, genetic breeding and prospects of P. ternata. The impact of germplasm resources and biogeography are the key factors of the effects of traditional Chinese medicinal materials, avoiding the medical negligence caused by using the confused medicine. Genetic diversity and genetic breeding are the basis of germplasm improvement. A virus-free technique of tissue culture is used to rapid propagation of P. ternata, promoting the production of seedlings without season restrictions. Functional gene research is the theoretical basis and target of germplasm improvement. Many genes, such as PtsHSP17.2 and PtSAD have been confirmed to play an important role in heat stress, guiding the selection and breeding of heat-resistant and drought-resistant P. ternata resources. Still, some problems exist in the production of P. ternata, presenting a challenge in breeding and cultivation. We summarize previous studies here and propose directions for further study to advance the research in the production of P. ternata.